Adhesion Behavior of Chondrocyte and Osteoblast on Surface-Modified Biodegradable PLLA Films and Scaffolds - Choi, Jiyeon; Jung, Hyun Jung; Park, Bang Ju; Joung, Yoon Ki; Park, Kwideok; Han, Doug Keun (POLYMER SOC KOREA, 2012)
Surface-modified poly(L-lactic acid) (PLLA) films and scaffolds were treated with plasma discharge in oxygen gas and subsequently subjected to in situ grafting of acrylic acid (AA) in order to increase the cell compatibility. The surface of AA-grafted PLLA was converted to hydroxyapatite (HA)-deposited PLLA in stimulated body fluid (SBF). After the samples were immersed in phosphate-buffered saline (PBS), fetal bovine serum (FBS), normal saline, or cell medium, the water contact angles were significantly reduced on the surface of HA-deposited PLLA. Chondrocyte and osteoblast showed a higher attachment and cell proliferation on HA-deposited surfaces and in particular, it was confirmed that chondrocyte was considerably influenced by HA. However, osteoblast showed better cell proliferation on the surfaces immersed in FBS, cell medium or HA-deposited surface. In addition, the cell proliferation in 3D scaffolds was much higher than that on film type, irrespective of chondrocyte and osteoblast. Therefore, such surface-modified PLLAs are expected to be useful as organic-inorganic hybrid scaffolds in the regeneration of cartilage and bone.
Keywords: POLY(GLYCOLIC ACID); APATITE FORMATION; TISSUE; PROTEINS; DENSITY